Applications of management science in productivity, finance, and operations - Lawrence, Kennedy D.; Klimberg, Ronald K. (Emerald, 2006)
Volume 12 of the "Applications of Management Science" series is directed toward the applications of management science to: Multi-Criteria Decision Making, Operations and Supply Chain Management, Productivity Management (DEA), and Financial Management. This volume will prove valuable to researchers, practitioners and students of management science and operations research. It provides an overview of some of the most essential aspects of the discipline and is an excellent point of reference for persons interested in management or management science. It focuses on four key applications of management science, and is targeted towards a wide audience of researchers, practitioners, and students.
Keywords: Business & Economics -- Decision-Making & Problem Solving.; Social Science -- General.; Management decision making.; Society & social sciences.; Management science.; elektronické knihy; electronic books